2011
DOI: 10.1111/j.1460-6984.2011.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Botox® to reduce drooling in a paediatric population with neurological impairments: a Phase I study

Abstract: In the clinical setting of the Drooling Treatment Project, the results indicated that the context in which drooling occurs is an important factor and suggested the value of considering the situational context when making drooling judgments. Further, there was a difference in the pattern of response between the children with cerebral palsy and those with operculum syndrome, suggesting that aetiology may be involved in the response to Botox®.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…It is considered to have efficacy rates ranging from 89% to 95% when injected in both submandibular and parotid glands. BoNTs injections improve symptoms effectively but temporarily; patients usually require more than one injection for drooling control . The effect by injection varies from 6 weeks to 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered to have efficacy rates ranging from 89% to 95% when injected in both submandibular and parotid glands. BoNTs injections improve symptoms effectively but temporarily; patients usually require more than one injection for drooling control . The effect by injection varies from 6 weeks to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…BoNTs injections improve symptoms effectively but temporarily; patients usually require more than one injection for drooling control. 12,13 The effect by injection varies from 6 weeks to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, objective scales are time-consuming and impractical in the clinical settings (Alrefai, Aburahma, & Khader, 2009;Gok et al, 2013;Hay & Penn, 2011).…”
Section: Studies On Questionnaire-based Scalesmentioning
confidence: 99%
“…They also found that objective methods such as using dental rolls are difficult to carry out in children for fear of choking. In another study by Hay (2011), subjective rating scales were shown as non-aggressive qualitative tools for drooling measurement; they indicate drooling reduction in daily situations versus quantitative objective tools which only represent decrease of salivary flow that does not necessarily shows change of drooling severity.…”
Section: Studies On Questionnaire-based Scalesmentioning
confidence: 99%
“…The rate of improvement in drooling is directly proportional to the quantity of toxin administered. The effects of a higher dosage of botulinum toxin are unknown, and the effect of this drug is transitory, ranging from 6 weeks to 12 months …”
Section: Discussionmentioning
confidence: 99%